PENGARUH INFLASI, PENDAPATAN PERKAPITA, DAN TINGKAT BAGI HASIL DEPOSITO TERHADAP DEPOSITO BANK UMUM SYARIAH - Anwar, Cep Jandi; Juliasari, Widia Kartika (FEB Universitas Sultan Ageng Tirtayasa, 2016)
The aim of this study is to examine the effect of inflation, per capita income, and profit sharing deposits rate on islamic commercial bank deposits in Indonesia. We used period data from 2010 to 2013. The data was taken from the Central Statistic of Republic Indonesia and Bank Indonesia from Sharia Banking Statistic published. Metode of analysis in this study was Error Correction Model (ECM). The result showed that in the short term, inflation variabel had no significant effect on islamic commercial bank deposits in Indonesia, while per capita income and profit sharing deposits rate variabel was significant effect on islamic commercial bank deposits in Indonesia. In the long term inflation, per capita income and profit sharing deposits rate significantly on islamic commercial bank deposits in Indonesia. Keyword: Deposits, Inflation, Per Capita Income, Profit Sharing Deposits Rate, Error Correction Model